Socialni kapital samostojnih inovatorjev in dostop do znanja - Podmenik, Darka (Teorija in praksa, 2014)
This paper explores the importance of social capital for independent inventors' access to knowledge relevant to their innovation activity. The first part is theoretical and deals with types of social capital crucial to knowledge transfer. The second part presents the empirical, qualitative study of Slovenian independent inventors. Twenty-two semi-structured interviews were conducted and the findings point to independent inventors' limited access to those types of social capital which are important for knowledge transfer within the Slovenian innovation system. This is especially true for bridging and weak ties. As a result, independent inventors are not included in the knowledge flow; especially not the formally organised and collective knowledge which is needed to successfully carry out all phases of innovation. The conclusion of the paper suggests a few basic steps to bridge this gap.
Keywords: Družbena omrežja; Innovations; Inovacije; knowledge; prenos znanja; Social capital (Sociology); Social networks; socialni kapital; Socialni kapital (Sociologija); znanje